Radioulnar Ischaemic Necrosis in a Dog with Concurrent Osteomyelitis and Bone Sequestration - Aller, Theresa L.; Phillips, Kathryn L.; Kapatkin, Amy S.; Watson, Katherine D. (VCOT Open, 2020)
An 11-month-old intact female Golden Retriever presented for a 3- to 4-week history of right thoracic limb lameness. Computed tomography of the limb showed a sequestrum with a periosteal and endosteal reaction at the level of the nutrient foramen of the radius. Septic osteomyelitis was suspected based on cytology. Repeat examination and imaging revealed improvement in the lesion and resolution of the lameness. This lesion is similar to reports of radioulnar ischaemic necrosis, but is the first report with concurrent osteomyelitis and sequestration.
Keywords: radioulnar ischaemic necrosis; osteonecrosis; haematogenous osteomyelitis; sequestrum